Estudo bioclimático entre as condições do tempo e a malária na Amazônia Legal - Gomes, Ana Carla dos Santos (2011)
Advance knowledge of weather conditions can be very useful for helping society to avoid waste and loss of human and material resources. From a statistical analysis, we tried to find an association malaria and climatic variables in Amazonia. For this it is necessary to check whether there is a relationship, will be used monthly data of reported malaria and meteorological data for the period 2000 to 2009 thirteen municipalities of the Amazon. Malaria is one of the oldest human diseases most prevalent in the world, none can match her in the geographical distribution and the health of populations. For this reason, it is necessary to investigate the cycle of malaria with climate variability in the Amazon, since this region has the highest incidence of the disease in Brazil. The results showed different situations for the ideal situation of contagion, when analyzed together with the variables in different locations, showed a clear association between them. This study could be used to predict the situation of this disease, contributing to public policy avoiding economic and human waste.